Educational policies can strengthen climate coalitions - Max Bradley; Rens Chazottes; Susanna Garside; Nina Lopez-Uroz (Proceedings of the National Academy of Sciences, 2026)
Building public support for ambitious climate policies is a central challenge for governments seeking to decarbonize their economies. Many climate change mitigation policies impose visible material costs on citizens, and governments have limited fiscal capacity to deploy compensatory measures. Education is often used as a tool to build public awareness about climate change, but its effect on support for climate policies is not well understood. We evaluate the effects of a climate education policy through the study of a real-world large-scale educational intervention: a 3-h interactive workshop which has so far been implemented in over 500 French universities. We employed a randomized control trial reaching 1,845 students across 167 workshops. Students who took the workshop expressed 7 percentage points higher support for costly climate policies, including a beef tax, short-haul flight ban, and meat-free university canteen, compared with the control group. The workshop increased beliefs in the effectiveness of these policies and elicited more positive emotions about climate action. Evidence from a subsample of follow-up survey respondents suggests these effects may persist for at least 6 wk. We find no evidence that the workshop increases willingness to donate to a climate NGO. Overall, the results suggest that well-designed climate education can play a role in broadening public coalitions for ambitious climate policies by strengthening perceived policy effectiveness and support for costly policies.